Genetic diversity and phylogenetic analysis of ADRB2 gene in Awassi and Karakul sheep: Genetic diversity in Karakul and Awassi sheep - Jassim, ZM; Aljubouri, TRS; Al-Shuhaib, MB (Journal of the Hellenic Veterinary Medical Society, 2025)
Due to the importance of the ADRB2 (adrenergic receptor beta 2) gene in a wide range of metabolic activities, it was aimed to evaluate its potential to differentiate between the Iraqi Awassi (n=88), and the Iranian Karakul (n=84) sheep. Twenty-seven variants were identified, including fourteen insertion variants, which constituted 51.9% of the total polymorphisms. Additionally, nine silent SNPs (33.3%) and four missense SNPs (14.8%) were detected. The analysis of genetic diversity revealed that Karakul showed a higher number of haplotypes (h=16) and variable sites (v=11) compared with Awassi (h=13, v=9). The assessment of the evolutionary relationship among the examined populations was conducted utilizing molecular variance analysis, which indicated that the predominant diversity observed stemmed from variations within populations (76.55%), while variations between populations accounted for a mere 23.45%. The median-joining network illustrated that Karakul harbored 11 haplotypes and Awassi had 8 haplotypes, segregated into distinct groups based on their respective breeds, with 5 haplotypes showing shared localizations. Extensive phylogenetic information unveiled that the Chinese origin was the sole precursor to all identified haplotypes. Considering the ADRB2 gene's capacity to distinguish between the crucial Middle Eastern breeds, it is strongly advised that it be utilized as a robust biological marker for tracing biological diversity across broader ovine sequences.